2021
DOI: 10.1021/acsami.1c09232
|View full text |Cite
|
Sign up to set email alerts
|

Paramagnetic Mn8Fe4-co-Polystyrene Nanobeads as a Potential T1–T2 Multimodal Magnetic Resonance Imaging Contrast Agent with In Vivo Studies

Abstract: In developing a cluster-nanocarrier design, as a magnetic resonance imaging contrast agent, we have investigated the enhanced relaxivity of a manganese and iron-oxo cluster grafted within a porous polystyrene nanobead with increased relaxivity due to a higher surface area. The synthesis of the cluster-nanocarrier for the cluster Mn 8 Fe 4 O 12 (O 2 CC 6 H 4 CHCH 2 ) 16 (H 2 O) 4 , cross-linked with polystyrene (the nanocarrier), under miniemulsion conditions is described. By including a branched hydrophobe, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…As an example, inorganic and polymeric nanoparticles that showed a minimal hemolytic response in the presence of erythrocytes were developed. 1,13,14 Other researchers have likewise demonstrated a significant decrease in the toxicity of polystyrene nanoparticles by forming a protein corona. 15 Additionally, studies found that forming a protein corona around nanoparticles increases the colloidal stability of metal nanoparticles.…”
Section: Introductionmentioning
confidence: 97%
“…As an example, inorganic and polymeric nanoparticles that showed a minimal hemolytic response in the presence of erythrocytes were developed. 1,13,14 Other researchers have likewise demonstrated a significant decrease in the toxicity of polystyrene nanoparticles by forming a protein corona. 15 Additionally, studies found that forming a protein corona around nanoparticles increases the colloidal stability of metal nanoparticles.…”
Section: Introductionmentioning
confidence: 97%
“…We were surprised to discover that rather than enhancing the T 2 contrast, the relaxivity r 1 increased to 3.37 mM –1 s –1 and there was a decrease in r 2 to 11.07 mM –1 s –1 . This effect was amplified by increasing the porosity of the polymer nanocarrier, where the greater surface area led to an increase in relaxivity to an r 1 of 5.2 ± 0.1 mM –1 s –1 and r 2 increasing to 50.1 ± 4.8 mM –1 s –1 , with capabilities for T 1 and T 2 dual contrast . The Mn 8 Fe 4 -coPS nanobeads (see Figure ) have exhibited low cytotoxicity, increased blood circulation time, limited biodistribution, in vivo MR imaging, and in vivo integrity, based on synchrotron X-ray fluorescence microscopy .…”
Section: Introductionmentioning
confidence: 98%
“…24 This effect was amplified by increasing the porosity of the polymer nanocarrier, where the greater surface area led to an increase in relaxivity to an r 1 of 5.2 ± 0.1 mM −1 s −1 and r 2 increasing to 50.1 ± 4.8 mM −1 s −1 , with capabilities for T 1 and T 2 dual contrast. 25 The Mn 8 Fe 4 -coPS nanobeads (see Figure 3) have exhibited low cytotoxicity, increased blood circulation time, limited biodistribution, in vivo MR imaging, and in vivo integrity, based on synchrotron X-ray fluorescence microscopy. 25 Where the outer-sphere mechanism is a diffusion-dependent process, 26 these results suggest that surface-bound clusters contribute to the relaxivity in an inner-sphere-type mechanism involving direct and indirect interactions of water with the metal of the cluster.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bio-nanotechnology, particularly with the usage of nanoparticles, has led to promising results in cancer diagnosis and treatment. 1 For example, paramagnetic Mn 8 Fe 4 - co -polystyrene nanobeads have the potential to be used as the exogenous contrast agent for T1–T2 magnetic resonance imaging, 2 and Fe 3 O 4 /TiO 2 nanocomposites could be introduced to enhance radiation effects in neuroblastoma treatment. 3 Despite the great potential of bio-nanotechnology, gaining insights into the interactions between nanomaterials and subcellular structures is crucial prior to their wide applications in vivo .…”
Section: Introductionmentioning
confidence: 99%